BIOLARVASIDA EKSTRAK METANOL DAUN - Siti Zulaihah, ; Sri Hidayati Syarief, (Matematika dan Sains, 2011)
The proposes of reseach are (1) to know the biolarvaside activity of tapak daras methanol extract against Aedes aegypti larva, (2) to know effect of tapak daras methanol extract to lethality degree of Aedes aegypti larva. In this research extraction was conducted by maceration, the kinds of the secondary metabolites constituent were identified by qualitative test, and biolarvaside test using Aedes aegypti larva. Based on the research, the LC50 value of tapak daras methanol extract was 1804.82 ppm. The ANOVA analysis showed that concentration of tapak daras methanol extract enfluenced the lethality degree of Aedes aegypti larva. The higher the concentration of tapak daras methanol extract, the higher the lethality degree of Aedes aegypti larva.50 value of tapak daras methanol extract was 1804.82 ppm. The ANOVA analysis showed that concentration of tapak daras methanol extract enfluenced the lethality degree of Aedes aegypti larva. The higher the concentration of tapak daras methanol extract, the higher the lethality degree of Aedes aegypti larva.